Synergistic effect of intumescent flame retardant and zinc borate on linear low‐density polyethylene. Issue 11 (18th September 2021) - Mu, Jing jing; Zhou, Ru; Liu, Chang; Su, Teng
Abstract: A series of novel intumescent flame retardant (IFR) based on melamine, neopentyl glycol, and aluminum diethylphosphinate were prepared and tested. In addition, the synergistic effect of the novel IFR and zinc borate (ZB) on the flame retardancy of LLDPE composites was investigated. The structures of novel IFR and ZB were characterized by X‐ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The limiting oxygen index (LOI) increased from 19.3% for the pure LLDPE to 27% for the 25 wt% IFR/5 wt% ZB composites and the composites achieved the desired V‐0 rating in the UL‐94 test. Thermogravimetric analysis showed that the addition of IFR/ZB reduced the pyrolysis rate of the LLDPE composites at high temperatures and increased the amount of the char residues, and the char residue of LLDPE‐5 reached 12.1 wt% at 700°C. Cone calorimetry (CCT) data showed that the peak of total heat release, heat release rate, and fire growth index were comparatively reduced, indicating that the addition of IFR/ZB decreased the fire hazard of LLDPE composites. The formation of a compact and thermally stable char layer on the surfaces of LLDPE composites was revealed from the scanning electrone microscopy images and digital photographs of the char residue after the CCT tests. Abstract : Synergistic effect of intumescent flame retardant and zinc borate on linear low‐density polyethylene.